The XACML Standard: addressing architectural and security aspects - Pereira, Óscar Mortágua
The OASIS XACML (eXtensible Access Control Markup Language) standard defines a language for the definition of access control requests and policies. It is intended to be used with ABAC (Attribute Based Access Control). Along with the language, the standard defines an architecture, workflow and evaluation mechanism. When implementing real scenarios, developers can come across with the missing of several issues not addressed by the standard. For example, the architecture proposed defines the workflow but does not define the way components should be distributed over different machines. Additionally, the standard does not include any information about how securing communications between components. This paper proposes a solution to deal with the aforementioned gaps. A proof of concept is also presented in an IoT use case in the context of the European project: SMARTIE – secure and smarter cities data management.